Pengaruh Model Pembelajaran Project Citizen terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Pendidikan Pancasila dan Kewarganegaraan - Mukhlisotin, Faridhotul Alfiyah (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to implement project citizen learning and analyze the effect of the project citizen learning model on students' critical thinking skills. This study utilized a quasi-experimental method through the independent sample t-test with the N-Gain Score test to determine the difference in critical thinking skills between the experimental control class and the class. Project citizen learning was implemented through six stages: problems, problem selection as discussion material, data collection, portfolio development, portfolio presentation, and learning reflection. The project citizen learning model significantly affected students' critical thinking skills in Civics subjects with a significance value of less than 0.05, namely 0.000 < 0.05. Students had changed for the better after applying the project citizen learning model.